Perumusan Model Koordinasi Penanganan Jalan Aantar Wilayah DI Era Otonomi Daerah - Achmad Nadjam; Desi Supriyan (Politeknik Negeri Jakarta, 2010)
Abstract After area autonomy prevailed, local governments in South Sumatra and Lampung are impressed to have high enough sector tendency in handling highway network. Every local government not only in sub-province/city but also in province, develops, improves and protects the highway network which is his/her authority. Province government has authority of province road, and sub-province/city government has authority of sub-province/city road, so that sometimes, the agreement in the planning of highway network system can not be reached. The purpose of this research is to formulate the models of coordinate handling road between region which is appropriate for the condition in Indonesia. The method that is used in this research is reexamination about road management which is evaluated from 3 aspects that is, institutional aspect, financing aspect, and regulation aspect. These three aspects are correlated with area autonomy, so that the model of handling road coordination can be designed. The result and the conclusion from this research are in the form of coordinating model, such as: Top-down Principal Agency System. In this system, the planning and the developing (executing) of road which are based on master plan and financing, become center government’s responsibility through APBN or province government’s APBD, while local government is supporter. The type of road which is managed in this system is National road or Province road. Bottom-Up Principal Agency System. This system can be done if the local government has high financial, so that the local government has a role as the owner and financier, while the center government is just as sponsor through APBN. The type of road which is managed in this system is province road and sub-province road. Keywords : local government, province government, institutional aspect, financing aspect, regulation aspect.